2011
DOI: 10.1007/s10333-011-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater flow and transport and potential sources of groundwater nitrates in the Ryukyu Limestone as a mixed flow aquifer in Okinawa Island, Japan

Abstract: We investigated the groundwater flow and the transport and potential source of groundwater nitrates in the typical karst setting of the Ryukyu Limestone aquifer in the southern part of Okinawa Island, Japan. Analysis of groundwater hydrographs indicated that this is a ''mixed flow'' aquifer with the coexistence of slow diffuse flow in the matrices and rapid conduit flow in the caves and caverns. This relationship is indicated by the travel time of groundwater flow: 70 days in the matrices of the aquifer and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The anthropogenic source of NO 3 − and SO 4 2 − in the groundwater in the study area has been reported to be chemical fertilizer, (NH 4 ) 2 SO 4 , used in the catchment (e.g., Yoshimoto et al, ; Yoshimoto et al, , ; Nakano et al, ; Yasumoto, Hijikawa, Nakaema, Towata, & Nakano, ). NO 3 − and SO 4 2 − are formed by the dissolution and nitrification of (NH 4 ) 2 SO 4 , according to Equation (e.g., Kondo, Tase, & Hirata, ): NH42SO4+4O22NO3+SO42+2H2normalO+4H+ Because H + ions form according to Equation , limestone can dissolve.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The anthropogenic source of NO 3 − and SO 4 2 − in the groundwater in the study area has been reported to be chemical fertilizer, (NH 4 ) 2 SO 4 , used in the catchment (e.g., Yoshimoto et al, ; Yoshimoto et al, , ; Nakano et al, ; Yasumoto, Hijikawa, Nakaema, Towata, & Nakano, ). NO 3 − and SO 4 2 − are formed by the dissolution and nitrification of (NH 4 ) 2 SO 4 , according to Equation (e.g., Kondo, Tase, & Hirata, ): NH42SO4+4O22NO3+SO42+2H2normalO+4H+ Because H + ions form according to Equation , limestone can dissolve.…”
Section: Resultsmentioning
confidence: 99%
“…The Shimajiri mudstone layer has an impermeable basement, and the Ryukyu limestone layer, which is 20 to 80 m thick, serves as an aquifer. These layers are transected by faults, and the Ryukyu limestone aquifer can be separated into several permeable blocks by a conjugate fault system with strike directions showing predominantly NE-SW and NW-SE orientations; the stepwise geological structure is shown in Figure 1 Imaizumi, Okushima, Shiono, Takeuchi, & Komae, 2002;Sagae et al, 2012;Yoshimoto et al, 2007;Yoshimoto, Tsuchihara, Ishida, & Imaizumi, 2011a, 2011b. The blocks are characterized by their double porosity, a matrix-and-fracture system, and caves.…”
Section: Site Description and Hydrogeological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…When surface water is scarce, the water requirements for domestic and agricultural purposes are fulfilled primarily from GW [21]. For instance, on Miyako Island in Okinawa, drinking water availability depends on the rainwater accumulated underground [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In such areas, strategies for the sustainability and development of agriculture, along with the incorporation of appropriate groundwater resource management are needed (Van der Velde et al 2007, Nawa & Miyazaki 2009, Ishida et al 2011, Yoshimoto et al 2011, Duncan 2012, Kobayashi & Koda 2012, Baharuddin et al 2013, Koda et al 2014. Shirahata et al (2014) estimated hydraulic properties of an unconfined aquifer on an island where groundwater development was desired for agricultural use.…”
Section: Introductionmentioning
confidence: 99%